SURVEI PENGGUNAAN ALAT KONTRASEPSI PADA PASANGAN USIA SUBUR PENYANDANG DISABILITAS NETRA PADA MASA PANDEMI COVID-19: Survey Of Contraception Use In Couples Of Fertilized Age With Vision Impairment During The COVID-19 Pandemic - Sunesni; Ilham Akerda Edyyul; Dian Furwasyih (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2023)
Limited access to family planning services, especially in Indonesia, poses a threat to the occurrence of discontinuation of contraceptive use and unwanted pregnancies. This condition also occurs in the disabled group. Meanwhile, there are still common misconceptions about persons with disabilities who are considered unable to have sexual relations, cannot get pregnant, or form a family. Therefore, people with disabilities are considered not to need to use and obtain information about contraceptives. This condition causes low knowledge of persons with disabilities. The purpose of this study was how to use contraception devices for couples of childbearing age (EFA) with blind disabilities in Padang City during the COVID-19 Pandemic. This type of research is descriptive which was carried out in the city of Padang through the association of the Board of Directors of the Indonesian Blind Association (DPC Pertuni) Padang City. The samples used in this study were all couples of childbearing age (PUS) with blind disabilities totaling 40 people who were members of the DPC Pertuni, Padang City. The results of this study found that from 40 respondents, 32 people (80%) respondents had a sufficient level of knowledge, 8 people (20%) were categorized as lacking, while for the use of contraception most of the respondents chose to use injection contraception, as many as 16 respondents. (40%) and there are still many respondents who do not use contraception as many as 14 respondents (35%). From these results, it is necessary to provide counseling activities that are easily accessible to PUS with visual impairments through the nearest health institution by directly providing information about reproductive health, sexuality, and family planning to persons with disabilities during regular meetings between members of persons with disabilities.